Investigation of the Optimal Layout of the Roadway in Closely Spaced Ultra-Thick Coal Seams Mining with Remaining Coal Pillars - Bin Zhao; Le Gao; Xianghui Tian; Yingyu Sun (Shock and Vibration)
The reasonable layout of the roadway in closely spaced, ultra-thick coal seam mining is of great significance to mining safety. Based on the research background of repeated roof leaks in the process of repairing the return air roadway in working face No. 30503 in the Tashan Coal Mine, theoretical analysis, in situ engineering testing, and numerical simulation were jointly adopted to evaluate the stability of the return air roadway under two schemes of repairing the original return air roadway and excavating a new return air roadway. The results show that the vertical mining-induced fissure above the roadway will cause severe damage to the roadway due to the influence of working-face mining when restoration of the roadway excavation is adopted. When choosing to excavate a new return air roadway, the new return air roadway just staggers the vertical cracks located in the top slab of the original return air roadway, putting the roadway in a state of stress reduction, making the roadway itself more stable and conducive to support. Therefore, the new air return tunnel was selected to establish the working face. To ensure safety of the working face during the mining of the original return air roadway, the original return air roadway was filled with high water content materials. Site investigation data show that this material plays a cushioning role in the filling section of the original return air roadway during the mining of the 30503 working face, and the deformation of the new return air roadway during the filling section crossing the original return roadway is stable and well controlled.